El edificio de apartamentos Art Deco en La Habana - González Couret, Dania (Revista Científica de Arquitectura y Urbanismo, 2013)
RESUMEN PALABRAS CLAVE The Art Deco Apartment Building in Havana ABSTRACT : Despite the Art Deco style it is not considered today as part of the Modern Movement, it was identified as the first expression of Modern Architecture starting in 1927 in Cuba, having the apartment building as one of its main architectural programs. The present article deals with the joint beginning of both, the Art Deco style and the modern apartment building in Havana. It departs from the spatial transformations carried out in the apartment building and the opportunities offered by the indented volume with emphasis in verticality, proper of this architectural style. Based on two significant case studies, the evolution of the Art Deco apartment building in Havana is shown, concluding that beyond the cultural, historical and aesthetical values, this legacy constitutes an important reference, because of the volumetric and spatial solution that its architectural design offers as guarantee of the indoor environmental quality. KEY WORDS : housing, apartment buildings, art deco architecture. : vivienda, edificios de apartamento, arquitectura Art Deco. : A pesar de que hoy no se considera parte del Movimiento Moderno, el Art Deco fue identificado como la primera expresión de la arquitectura moderna asumida a partir de 1927 en Cuba, la cual tuvo en los edificios de apartamentos uno de sus programas más favorecidos. En el presente artículo se aborda el nacimiento conjunto del Art Deco y el moderno edificio de apartamentos en La Habana, a partir de las transformaciones espaciales que sufrió el apartamento y las oportunidades que ofrecía el volumen grecado con énfasis en la verticalidad que este estilo arquitectónico ofrecía. A partir del estudio de dos casos significativos, se muestra la evolución del edificio de apartamentos Art Deco en La Habana y se concluye que más allá de sus valores culturales, históricos y estéticos, este legado constituye un importante referente por la solución volumétrico-espacial que su diseño arquitectónico ofrece como garantía de la calidad ambiental interior.